Evaluation of plant growth regulators on root formation of semihardwood and hardwood cuttings of Sarcandra glabra (Thunb.) Nakai - En, Le Hong; Nguyen, Nguyen Thanh; Thanh, Giang Thi (Academia Journal of Biology, 2016)
The aim of this study is to evaluate the effects of three types of plant growth regulators (α- naphthyl acetic acid, indole-3-acetic acid and β-indol butyric acid) on the root formation of the semihardwood and hardwood cuttings of Sarcandra glabra (Thunb.) Nakai. The effects of plant growth regulators on root formation were evaluated based on living percentage, rooting percentage, secondary rooting percentage, and the number and the length of roots. The results showed that the best root growth regulator was β-IBA. The overall effective concentrations of growth regulators were 1.0 and 1.5%. The living percentage of the semihardwood cuttings was lower than that of the hardwood cuttings. However, the root growth parameters of the semihardwood cuttings were better than those of the hardwood cuttings.